Evaluation of the influence of exposure index on image quality and radiation dose - Moey, Soo Foon; Mohamad Asri, Fatin Naimah (Iranian Association of Medical Physicists (IAMP), 2019)
Introduction: The introduction of digital radiography has led to a significant problem with dose creep. To address the problem with dose creep, manufacturers have established a set of exposure indicators (EI) as a feedback mechanism to safeguard against overexposure. EI is the measure of incident exposure to the detector that is directly proportional to the signal-to-noise ratio and can be related to image quality. The aim of this study was to evaluate the influence of EI on image quality and radiation dose for posterioranterior (PA) chest radiography. Materials & Methods: This study was conducted in three phases; pre, experimental and post- optimization. A total of 60 patients that could fulfill the inclusion and exclusion clauses for PA chest radiography were recruited. The radiographic technical parameters, dose area product and EI were recorded. Radiographs were printed and the images were evaluated by two recruited radiologists using the modified evaluation criteria established by the Commission of European Communities, 1996. Results: Statistical analysis using Spearman’s Rho Correlation showed insignificant result between EI and image quality for PA chest radiography (p>0.05), conversely, there was a significant relationship between EI and radiation dose (p<0.05). Conclusion: EI can be used as an indirect measure of image quality and radiation dose. EI does not directly determine image quality as radiographic technique and parameters used can affect image quality. However, EI can be used as an indicative measure of radiation dose but it cannot provide an accurate measurement of radiation received by the patient.